Értékek változásai Magyarországon 1978-1993: Kontinuitás és diszkontinuitás a kelet-közép-európai átmenetben (Szociológiai Szemle, 2024)
Beginning in the late 1970s, the Centre for the Sociological Study of Values at the Institute of Sociology of the Hungarian Academy of Sciences under the direction of Elemér Hankiss conducted a series of surveys on the value systems and priorities of Hungarians with the purpose of mapping their distribution and explaining their changes. The collaborators in this project were Róbert Manchin, László Füstös, and Árpád Szakolczay. The present paper discusses four questions, The first concerns the smoothness of change in the course of these fifteen years, taking into consideration that the shift to the new regime is generally assumed to have taken place without major dislocations in Hungary. Confronting this general view with the available data, the authors examine the kind of values have changed in such a gradual fashion. Secondly, the authors consider whether a transition in the opposite political direction would not have conformed to certain existing values, and whether certain trends, perceptible during the old regime, could survive the changes. Thirdly, apart from these issues of continuity, particular attention is paid to those values for which the year 1990 represented a clear break. Finally, the question is raised whether the emergence of any significant trends between 1990 and 1993 can be documented or rather stability in trends, preferences, and structures and even a perceptible return to former ways of acting and thinking predominate.The analysis assesses the changes in the value priorities of Hungarians between 1978 and 1993 and attempts to ascertain if there were any major shifts in the structure of value preferences during that period.